Adaptive capacity of the Maine lobster fishery: insights from the Maine Fishermen's Climate Roundtables - Ellie Mason; Anne H. Beaudreau; Suzanne N. Arnold; Sam Belknap; Emma D. Scalisi (Canadian Science Publishing, 2024)
The Gulf of Maine in the northwestern Atlantic Ocean is one of the world's fastest warming marine regions. Changes in ocean conditions are affecting growth, survival, and distribution of American lobster (Homarus americanus), which supports iconic fisheries along the coast of Maine, USA. In this study, we analyzed 15 years of oral records from the Maine Fishermen's Climate Roundtables to explore fishermen's observations of and responses to social-ecological changes. Fishermen reported an overall shift in lobster biomass further east and offshore, resulting in strategic expansion of fishing seasons and areas. Biomass shifts were thought to be connected to increases in temperature, decreases in salinity, a shift in ocean currents, and a loss of predator species. Fishing strategies were categorized according to five domains of adaptive capacity, but the majority of fishers' responses fell into two domains: "access to assets" and "diversity and flexibility". Strategies within these domains included increased expansion into federal lobster fisheries and extension of fishing seasons. Fishermen highlighted data gaps that need to be addressed to meet the challenges of climate change. Fisheries learning exchanges, such as the Climate Roundtables, create social networks that foster knowledge sharing to support the continued viability of local livelihoods.